EVALUATING THE IMPACT OF RECRUITMENT METRICS ON EMPLOYEE TURNOVER AND RETENTION RATES - Bhimanatham, Amarnath; Iyer, Subramaniam Seshan (International Journal of Research -GRANTHAALAYAH, 2025)
This research evaluates the impact of recruitment metrics on employee turnover and retention rates across various organizations. By analyzing key recruitment indicators such as time-to-fill, cost-per-hire, quality-of-hire, and source-of-hire, the study identifies their significant correlation with turnover and retention outcomes. The findings suggest that high-quality hires and strategic sourcing methods, such as employee referrals and internal job postings, lead to lower turnover rates and higher retention. A multiple regression model further underscores the predictive power of recruitment metrics in shaping workforce stability. The study emphasizes the importance of using recruitment analytics to refine hiring strategies, reduce turnover, and improve long-term employee retention.